CASH FLOW MANAGEMENT AND INVESTMENT DECISION-MAKING IN THE CORPORATE FINANCE SYSTEM - Utemuratova Magrifa Perdebaevna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
The article explores the theoretical and practical aspects of cash flow management and investment decision-making within the corporate finance system. In the context of intensifying market competition and evolving macroeconomic conditions, effective cash flow management serves as a crucial factor in ensuring financial resilience and enhancing company value. The study examines contemporary approaches to planning and optimizing operating, investing, and financing cash flows, as well as methods for evaluating investment projects with due consideration of risk and the cost of capital. The findings demonstrate that the integration of budgeting systems, financial forecasting, and investment analysis contributes to greater transparency in financial policy, strengthens liquidity management, and supports sustainable business growth.